Determinants Of Interest In Public Accounting Careers Among Undergraduate Accounting Students: A Case Study at Upn Veteran East Java - Aprilia, Anisa; Ratnawati, Dyah (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose : This study aims to identify and analyze the factors that influence undergraduate accounting students' interest at the National Development University